Synthesis, Anti-HIV and Anticancer Activities of Some New Formazans - Bhardwaj, S.D.; Jolly, V.S. (Asian Journal of Chemistry, 2010)
1-(Phenyl-3-(2-methyl-4-NN´-bis-2´-cyanoetbyl-aminophenyl) 5-chlorosalicylformazans have been synthesised by first reacting 2-methyl-4-NN´-bis-2´-cyanoethylamino-benzaldehyde with 5-chlorosalicylhydrazide which gave respective acidhydrazone. The acidhydrazone on treatment with diazotised aromatic amines in pyridine medium furnished formazans in 30 to 85% yield. Three derivatives of the formazans have been prepared by the reaction of the formazans with acylchlorides under Schotten-Baummanm reaction conditions.